URGENSI PROGRAM GERAKAN LITERASI DESA DI INDONESIA - Arief Prayitno (Universitas Jenderal Ahmad Yani, 2024)
This article discusses the urgency and appropriateness of the Village Literacy Movement in Indonesia, addressing various complex challenges related to education levels, resource access, and infrastructure in rural areas. The research aims to examine how literacy programs can enhance the quality of life and economic opportunities for village communities. Using a qualitative exploratory approach, the study finds that low formal education levels, limited access to reading resources, and a shortage of teachers and educational facilities are major barriers to improving rural literacy. Active participation from local government and communities in supporting literacy programs is crucial for their success. Additionally, tailoring literacy programs to local needs and characteristics is considered essential for their effectiveness. Digital literacy and financial literacy are identified as key aspects in the economic empowerment of villages, enabling communities to better utilize technology and manage finances. The findings of this study indicate that village literacy not only aims to improve reading and writing skills but also to empower village communities to access important information that can enhance their quality of life. With improved literacy, village communities are expected to engage more actively in productive and sustainable economic development. Therefore, collaboration between the government, educational institutions, and local communities is vital to creating an environment that comprehensively supports the enhancement of village literacy.